Предмет: Алгебра,
автор: gogiiv5552maxach
Преобразуйте в многочлен выражение
1) (x-2y)(3x+y)(x-y)
2) (x квадрат - 3y+2)(x квадрат +3x+2)
Ответы
Автор ответа:
0
3x^2-6xy+xy-2y^2(x-y)=
=3x^3-6x^2y+x^2y-2y^2x-3x^2y+6xy^2-xy^2+2y^3=
3x^3-8x^2y+3xy^2+2y^3
=3x^3-6x^2y+x^2y-2y^2x-3x^2y+6xy^2-xy^2+2y^3=
3x^3-8x^2y+3xy^2+2y^3
Похожие вопросы
Предмет: Алгебра,
автор: alexklyyk
Предмет: Математика,
автор: mahazakrevskaa
Предмет: Обществознание,
автор: frenkfrenk5535293
Предмет: Математика,
автор: mordovia10
Предмет: Биология,
автор: рааааак